Investigating the effect of parameters in the thermodynamic analysis of the solid oxide fuel cell cycle using response surface methodology - Hadi Ghaebi; Elahe Soleymani (Scientific Reports)
Abstract In this article, the effect of parameters in the solid oxide fuel cell cycle has investigated using the response surface method. The thermodynamic modeling of this cycle has been done by EES software, which by considering three variables (current density, molar flow rate and fuel cell temperature) as input parameters, to examine the mutual effects of parameters on the objective functions (net output power and exergy efficiency) using the experimental design method. According to the results of thermodynamic analysis, the net power output and exergy efficiency of solid oxide fuel cell are 2424 kW, 52.29% and 50.43%, respectively. By transferring the tests based on the central composite design for the parameters obtained by the Design Expert software, the extracted results show the interaction effect of the input parameters. According to the results of the regression analysis, the values ​​of R2 in the responses of net output power and exergy efficiency are 96% and 87.79%, respectively, which shows the accuracy of the model. The parameters have a good interaction effect with each other and the optimal points for the input parameters of current density (i), input methane molar flow rate (nCH4) and solid oxide fuel cell temperature (TSOFC) has been calculated at the points of 2311.53 A/m2, 0.0068 kmol/s and 1200 K, as well as the responses of net output power and exergy efficiency at points 3555.18 kW and 0.68345%.